Single-mode hollow-core photonic crystal fiber made from soft glass - Jiang, Xin; Euser, T. G.; Abdolvand, Amir; Babic, F.; Tani, Francesco; Joly, Nicolas; Travers, J. C.; Russell, Philip St. John (Optics Express, 2011)
We demonstrate the first soft-glass hollow core photonic crystal fiber. The fiber is made from a high-index lead-silicate glass (Schott SF6, refractive index 1.82 at 500 nm). Fabricated by the stack-and-draw technique, the fiber incorporates a 7-cell hollow core embedded in a highly uniform 6-layer cladding structure that resembles a kagomé-like lattice. Effective single mode guidance of light is observed from 750 to 1050 nm in a large mode area (core diameter 30 µm) with a low loss of 0.74 dB/m. The underlying guidance mechanism of the fiber is investigated using finite element modeling. The fiber is promising for applications requiring single mode guidance in a large mode area, such as particle guidance, fluid and gas filled devices.
EAM Import::2019-03-13